Utilization of Social Media Marketing and Word of Mouth and Their Impact Towards Increasing New Student Acceptance at The Karya Anugerah Education Foundation. - agustina; Sri Rezeki (PROCEEDING INTERNATIONAL BUSINESS AND ECONOMICS CONFERENCE (IBEC), 2023)
This study aims to determine the use of Social Media Marketing and Word of Mouth to Increase Acceptance of New Students of Karya Anugerah Education Foundation. The research method used is quantitative research with survey methods that use questionnaires as research instruments to collect data. The population in this study is the number of students who register Karya Anugerah Education Foundation in 2023 with a population of 182 students, The sample in this study is 125 students. Multiple linear regression research tests are used as an analytical tool to find out how the influence between independent and dependent variables. The results of this study show that both partially and simultaneously the variables of Social Media Marketing and Word of Mouth have a significant effect on increasing the acceptance of new Karya Anugerah Education Foundation. Social Media Marketing and Word of Mouth variables were able to explain the variation that occurred in the Increase in Acceptance of New Students by 62.9%. This is due to the use of Social Media Marketing and Word of Mouth to increase the acceptance of new students.